Illuminations of the Tabernacle of Moses and of Ezra in the Codex Amiatinus (Florence, Biblioteca Medicea Laurenziana, Amiatino 1): Bede, Cassiodorus and the Antiquitates Judaicae of Flavius Josephus. (26th April 2019) - Wander, Steven H.
Abstract: Features of the two illuminations from the first quire of the Codex Amiatinus, the bifolium of the tabernacle of Moses (6v and 7r, formerly 2v/II and 7r/III) and the miniature of the Jewish priest Ezra, who is identified by inscription (2r, formerly 4r/V), correspond more closely with text from the Jewish Antiquities of Flavius Josephus than with the parallel accounts in Scripture. Cassiodorus had the Jewish Antiquities of Flavius Josephus rendered from Greek into Latin, referring to the seventh chapter (that is, chapter 6) of book 3 as the source for his illustration of the tabernacle of Moses; and this illumination, according to Bede, was available as a model at Wearmouth–Jarrow. It appears that Bede also took part in fashioning the miniature of Ezra, both the verse inscription and the image itself, which also reflects more closely passages from Cassiodorus' so-called Latin Josephus than the corresponding sections of the Bible.